EFEKTIVITAS GAME BASED LEARNING DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN IPS KELAS VIII-D SMP NEGERI 56 SURABAYA - Salfianti; Nugroho Hari Purnomo; Arin Yudiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research was motivated by students' low interest in learning in Social Sciences (IPS) learning which tends to be boring. This research aims to measure the effectiveness of game-based learning in increasing students' interest in learning in class VIII-D in social studies subjects at SMP Negeri 56 Surabaya. This research uses a pre-experimental design with an instrument in the form of a learning interest observation sheet. The research results showed that there was a significant increase in all aspects of students' learning interest after implementing game-based learning, namely in the aspects of feelings of pleasure, interest, attention and involvement. These findings indicate that game-based learning can be an attractive alternative for increasing students' learning motivation in social studies subjects which tend to be considered less interesting.